2019 IEEE Intelligent Transportation Systems Conference (ITSC) 2019
DOI: 10.1109/itsc.2019.8917501
|View full text |Cite
|
Sign up to set email alerts
|

Response of Vulnerable Road Users to Visual Information from Autonomous Vehicles in Shared Spaces

Abstract: Completely unmanned autonomous vehicles have been anticipated for a while. Initially, these are expected to drive only under certain conditions on some roads, and advanced functionality is required to cope with the ever-increasing challenges of safety. To enhance the public's perception of road safety and trust in new vehicular technologies, we investigate in this paper the effect of several interaction paradigms with vulnerable road users by developing and applying algorithms for the automatic analysis of ped… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…For example, Schneemanne and Gohl [67] found that over half of test drivers who drove at 30 km/h and 50 km/h initially braked at a TTC of 3 to 4 s. In addition, all the participants braked at the reaction threshold of 2.5 s. Alvarez et al. [77] found that 71.7% of pedestrians chose to cross the road at a TTCT of 2–8 s. Some researchers have indicated that observers can directly perceive special information such as τ to determine whether they are on an impending collision course [11, 78]. The variable τ has inspired research to study judgements based on the time remaining.…”
Section: Driver Risk Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Schneemanne and Gohl [67] found that over half of test drivers who drove at 30 km/h and 50 km/h initially braked at a TTC of 3 to 4 s. In addition, all the participants braked at the reaction threshold of 2.5 s. Alvarez et al. [77] found that 71.7% of pedestrians chose to cross the road at a TTCT of 2–8 s. Some researchers have indicated that observers can directly perceive special information such as τ to determine whether they are on an impending collision course [11, 78]. The variable τ has inspired research to study judgements based on the time remaining.…”
Section: Driver Risk Assessmentmentioning
confidence: 99%
“…Alvarez et al. [77] found that TTC estimation was influenced by the chromaticity of the human‐machine interface of the approaching vehicle.…”
Section: Driver Risk Assessmentmentioning
confidence: 99%
“…The framework was deployed in a real vehicle and tested in three experimental cases that showed a variety of communication messages to pedestrians in a shared-space scenario [6], [7]. The team investigated the automatic analysis of pedestrian body language and determined behavioral patterns, thereby enabling the assessment of the impact of the coexistence of AVs and other road users on general road safety in a shared space for vulnerable road users (VRUs) and vehicles [8]. The perception of a road situation as safe in an environment that potentially influences well-being is also a topic of research that makes it possible to determine several levels of trust, uncertainty, and fear [9].…”
Section: Driver-pedestrian Interactionmentioning
confidence: 99%
“…The behavior of pedestrians was analyzed, concluding that a communication system proves to be positive in the interaction between the pedestrian and the vehicle. Moreover, the behavior of pedestrians was further studied in [27], where the vehicle detected the pose of pedestrians in order to predict their intentions.…”
Section: Human Factorsmentioning
confidence: 99%